The Influence of a Cognitive Task on the Postural Phase of Gait Initiation in Parkinson’s Disease: An Electromyographic Based Analysis - Fernandes, Ângela (2017)
The aim of this study was to compare postural control strategies during gait initiation in single- and dual-task conditions in individuals in early stages of Parkinson´s Disease (PD). The activation timing of tibialis anterior occurred significantly later in the individuals with PD than in the controls (p=0.05), and a significant interaction between the groups, conditions and limbs was found (p=0.027). Differences between the single- and dual-task conditions were observed for the activation timing of the tibialis anterior (p=0.042) and for the magnitude of soleus (p=0.007), with lower values for the dual-task condition. Furthermore, not all the individuals followed the previously reported pattern of soleus inhibition followed by tibialis anterior activation. The duration of the mediolateral displacement of the centre of pressure was longer in the individuals with PD than in the controls (p=0.019). The anticipatory postural adjustments during gait initiation are impaired in PD and are expressed by an activation failure of tibialis anterior in both single- and dual-task conditions. Hence, it is important that during rehabilitation, intervention should concentrate on the TA.